»Suomen kielen suurin rikkaus ja ihanin ominaisuus.» Elias Lönnrotin johto-oppia - Pitkänen, Kaarina (Virittäjä, 2005)
Elias Lönnrots views on word formation by derivation (englanti) 1/2005 (109) Elias Lnnrots views on word formation by derivation The article examines the views of nineteenth-century folklorist and linguist Elias Lnnrot on the use of derivation in Finnish word formation. It makes particular reference to two of his unpublished manuscripts from the 1850s. The writer also discusses at a more general level the development of ideas on derivation in Finnish language research. Early Finnish grammars include descriptions of word formation and thus also derivation. This is presented from a synchronic perspective and concentrates on transparent derivatives. By contrast, the derivation material collected and presented by Lnnrot also includes many lexicalised opaque derivatives. This indicates Lnnrots approach to derivation and explains why he formed neologisms even from derivational affixes that were not productive at the time. Lnnrot believed that derivation is a grammatical and regular phenomenon and one that comes automatically to native speakers. He did not distinguish between productive and non-productive derivational affixes but instead appears to have considered that new words could continue to be formed using any of the existing derivative models. Lnnrot believed that language users are capable of understanding the meaning of such derivatives on the basis of the words root and context. Lnnrot wished to incorporate into the grammar and vocabulary of Finnish many of the word forms, even rare ones, that he had come across in Finnish dialects and related languages. It should be remembered that the boundaries between the dialects and standard Finnish and between Finnish and closely related languages were at that time still quite blurred for language users, and that standard Finnish was just emerging. As a philologist who had a decisive influence on the formation of standard Finnish, the views of Elias Lnnrot concerning derivation and its place within Finnish grammar are of particular interest. Kaarina Pitknen